Analisis aspek manajemen dan sumberdaya manusia studi kelayakan bisnis BMT UGT Nusantara - Sudibyo, Dimasqi Taufiq; Solekah, Nihayatu Aslamatis (Maliki Interdisciplinary Journal, 2024)
The aim of this research is to analyze the feasibility of management and human resource aspects at BMT UGT Nusantara Pujon Sub-Branch, Malang Regency. This research method uses qualitative methods with observation and documentation studies. The results of this research indicate that BMT UGT Nusantara Sub-Branch Pujon, Malang Regency is feasible in terms of management and human resources..